Why bitcoin can never be money - LeRoux, Chris (REVISTA PROCESOS DE MERCADO, 2014)
In On the Origins of Money (1892), Carl Menger explains that in a barter situation, some commodities are more commonly demanded than others, are more saleable. In order to overcome the double coincidence of wants, people naturally begin trading their goods first for a more saleable good in order to then trade for their final objective. Menger (1892) describes it thus, «Men have been led, with increasing knowledge of their individual interests, each by his own economic interests, without convention, without legal compulsion, nay, even without any regard to the common interest, to exchange goods destined for exchange (their “wares”) for other goods equally destined for exchange, but more saleable.» Lud-wig von Mises restated the same insight in Human Action (1940), «[Money] is the most marketable good which people acquire be-cause they want to offer it in later acts of interpersonal exchange. Money is the thing which serves as the generally accepted and commonly used medium of exchange.» As ever more people discovered the advantages of using a more saleable good in indirect exchange, one commodity became increasingly adopted until it eventually became money, the most marketable of all goods, the good that can generally be traded for all other goods within the market. As Menger said (1892), «And so it has come to pass, that as man became increasingly conversant with these economic advantages… those commodities, which relatively to both space and time are most saleable, have in every market become the wares, which it is not only in the interest of every one to accept in exchange for his own less saleable goods, but which also are those he actually does readily accept.»